Wet Dark Fluid Cosmological Model in Barber Self-Creation Theory of Gravitation - Wankhade, S. C.; Nimkar, A. S.; Pund, A. M. (Journal of Scientific Research, 2021)
This paper investigates a Bianchi type VIII cosmological model with wet dark fluid in Barber self-creation theory of gravitation. To get the determinate model of the Universe, we have assumed the relationship between metric coefficients R and S. Also, the behavior of the model in the radiation Universe and the physical implications of the model are discussed in detail.